The role of local government in achieving good corporate governance principles for the tourism sector in seruyan regency through innovative licensing services - Mukhlis, M.; Murhaini, Suriansyah; Kristanto, Kiki (Institute Of computer Science (IOCS), 2025)
This research aims to analyse the role of local government in realising Good Corporate Governance (GCG) in the tourism sector, particularly in Seruyan Regency. The method used is empirical juridical, which combines a statutory approach and an empirical approach. The statutory approach is carried out by examining various related regulations, such as Law Number 23 of 2014 concerning Regional Government, Law Number 10 of 2009 concerning Tourism, and other regulations that support sustainable tourism governance. Meanwhile, the empirical approach is used to evaluate policy implementation at the regional level, by collecting data through interviews with government officials and tourism businesses to understand the challenges in implementing GCG principles. The results show that although the local government has adopted GCG principles in tourism policy, there are still various challenges in its implementation. The main obstacles include a lack of transparency in the business licensing system, suboptimal coordination between agencies, and a lack of community participation in tourism management. In addition, limited budget and digital infrastructure are also obstacles in implementing more effective digitalisation-based policies. However, this study also found that collaborative efforts between local governments, businesses, and communities can improve the effectiveness of tourism sector governance in a more sustainable manner. The uniqueness and originality of this research lies in its analysis that connects the concept of GCG with tourism policies at the regional level, particularly in Seruyan Regency. Unlike previous studies that focus on legal aspects or governance theories, this research shows the actual challenges of implementing GCG principles in local governments.